Roughness controlled superhydrophobicity on single nanometer length scale with metal nanoparticles1. Issue 36 (23rd April 2015) - ten Brink, Gert H.; Foley, Nolan; Zwaan, Darin; Kooi, Bart J.; Palasantzas, George
<x xml:space="preserve">Abstract</x> Here we demonstrate water droplet pinning onto nanostructured surfaces via control of roughness on a single nanometer length-scale generated by deposition of preformed gas phase distinct copper nanoparticles on hydrophilic and hydrophobic surfaces.